1970
DOI: 10.1136/adc.45.242.506
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Calcium and Magnesium in Newborn Babies

Abstract: . (1970). Archives of Disease in Childhood, 45, 506. Plasma calcium and magnesium in newborn babies. Normal values for plasma calcium and magnesium levels during the first week of life, in breast-and bottle-fed babies, have been determined. It has been shown on the sixth day that plasma levels of calcium, magnesium, and protein are all significantly lower in bottle-fed babies than in breast-fed babies, while the reverse is true of the plasma inorganic phosphorus.The normal babies have been compared with 30 bab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The low serum sodium levels are in keeping with dilution in the intravascular compartment. It is more likely that the oedema is caused by salt and water retention when the Though the changes which occur in serum calcium and magnesium levels in the neonatal period have been studied by others (Gittleman et al, 1964;Harvey et al, 1970), there is little agreement on the precise values which should be accepted as abnormal. A serum calcium level of 7 mg/100 ml or below was chosen in this paper, and this is lower than has generally been accepted in the past (Keen, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…The low serum sodium levels are in keeping with dilution in the intravascular compartment. It is more likely that the oedema is caused by salt and water retention when the Though the changes which occur in serum calcium and magnesium levels in the neonatal period have been studied by others (Gittleman et al, 1964;Harvey et al, 1970), there is little agreement on the precise values which should be accepted as abnormal. A serum calcium level of 7 mg/100 ml or below was chosen in this paper, and this is lower than has generally been accepted in the past (Keen, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…No attempt has been made to define accurately normal serum magnesium levels. Harvey et al (1970), using atomic absorption spectrophotometry, showed a mean serum magnesium concentration of 1-4 mg/100 ml in 25 bottle-fed babies on the sixth day of life. However, the range of results was very wide, 0-85-1 9 mg/100 ml.…”
mentioning
confidence: 98%
“…Though the changes which occur in serum calcium and magnesium levels in the neonatal period have been studied by others (Gittleman et al, 1964;Harvey et al, 1970), there is little agreement on the precise values which should be accepted as abnormal. A serum calcium level of 7 mg/100 ml or below was chosen in this paper, and this is lower than has generally been accepted in the past (Keen, 1969).…”
mentioning
confidence: 99%
“…Before birth, the foetus has a constant supply of water and electrolytes from the mother across the placenta; foetal water and electrolyte homeostasis is largely a function of placental and maternal homeostatic mechanisms that is reflected in cord blood. 2 After birth neonate must rapidly assume responsibility for its own fluid and electrolyte homeostasis in an environment in which fluid and electrolyte availability and losses fluctuate much more widely than in utero. Moreover, for reasons that are not understood, the transition from foetal to neonatal life is associated with what have come to be accepted as normal changes in fluid and electrolyte balance.…”
Section: Introductionmentioning
confidence: 99%
“…These small changes in fluid and electrolyte quantity represent large proportionate changes in neonate because of neonate's small size. 1,2 The reference ranges of serum Calcium is usually established on the basis of the statistical distribution of results within a sample of population. 1 The studies done to find normal distribution levels of these electrolytes till date are very limited.…”
Section: Introductionmentioning
confidence: 99%